Sobre a ocorrência de Philornis angustifrons e P. deceptiva (Diptera, Muscidae) em ninhos de Suiriri affinis e S. islerorum (aves, tyrannidae), no cerrado do Distrito Federal, Brasil - Higgins, Barbara Fernandes (2005)
The first report of Philornis angustifrons and P. deceptiva infesting nests of Suiriri affinis and S. islerorum in area of Distrito Federal's savanna is presented. It is known that larvae of these species have a strict relationship of parasitism with birds. The pupae were collected after the abandonment of the nests and the flies emerged in a period of about 13 days.